PENGEMBANGAN MEDIA BERBASIS APLIKASI AKSI SINTA PADA PEMBELAJARAN KALIMAT DALAM TEKS DESKRIPSI BAGI PENYANDANG SPEKTRUM AUTISME - Nuni Febriyanti; Liliana Muliastuti; Reni Eriyani (Peneliti.net, 2023)
This study aims to develop sentence teaching material in the descriptive text using the Aksi Sinta application that is tailored to the needs of students with autsime spectrum in inclusive schools and adjusted to basic competencies that refer to Permendikbud No. 37 of 2018. This development research uses the research and development method (Research and Development). The product development model for sentence teaching materials based on the Aksi Sinta application uses the ADDIE model. The validators in this study were one material expert, one media expert, one Indonesian language teacher and seventh grade students with autism spectrum at SMPN 165 Jakarta. Collecting data in this study using observation and questionnaires. The development of the Aksi Sinta application on the description text sentence teaching material has been developed with the ADDIE development model only up to thestage development. The analysis stage produces students' needs in understanding sentence teaching material in the description text, while the competencies used in schools are guided by the 2013 curriculum which refers to Permendikbud No.37 of 2018. The quality of the Aksi Sinta application that has been developed gets a very decent category with a percentage of 85.31 % based on the average validator's assessment. The evaluation of material experts got a percentage of 78.25%, media experts 86.25%, and Indonesian teachers 91.43%. The student response after using this application is good with a percentage of 86.5%. The Aksi Sinta application has implications in learning media to facilitate students on the autism spectrum in learning sentences in the descriptive text.